Changes in Immigrants' Body Mass Index with Their Duration of Residence in Germany - Monika Sander (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper investigates how immigrants' Body Mass Index (BMI) changes with increasing years since migration in Germany. The data are drawn from three waves (2002, 2004, and 2006) of the German Socio-Economic Panel Study (SOEP). The results indicate a clear increase of the BMI with additional years in Germany for men and women.
Keywords: C23; I12; 330; Body Mass Index; immigrants; SOEP